Pengaruh Pemanfaatan Teknologi Informasi, Rasa Memiliki, Dan Sistem Pengendalian Intern Terhadap Akuntabilitas LPD Se- Kecamatan Ubud Gianyar - Ni Kadek Finny Asnitasari; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of information technology, ownership and internal control system on LPD accountability in Ubud Gianyar District. The population in this study were all employees in 32-LPD in Ubud Gianyar District with a total population of 356 employees. The sampling technique used in this study was purposive sampling, with the criteria having a working age of 5 years so that the sample selection was 32 LPD heads and 93 LPD employees. Data analysis used Multiple Linear Regression Analysis Method. Th results show that, the use of information technology, a sense of belonging and an internal control system has a positive and significant effect on the accountability of LPDs in the sub-district of Ubud Gianyar. It is hoped that future researchers when conducting similar research will be able to add variables that have not been included in this study in order to obtain a stronger influence